Molecular Survey of Hepatozoonosis in Natural Infected Dogs: First Detection and Molecular Characterisation of Hepatozoon canis in Kyrgyzstan - Altay, Kursat; Aydin, Mehmet Fatih; Aytmirzakizi, Ayperi; Jumakanova, Zarima; Cunusova, Ayday; Dumanli, Nazir (Kafkas Univ, Veteriner Fakultesi Dergisi, 2019)
Canine hepatozoonosis is a tick-borne protozoan disease and widespread in Europe, Africa, Asia and America. There is not any available data about the presence of Hepatozoon infections in dogs in Kyrgyzstan. In the study we aimed that investigate the presence of Hepatozoon canis and the prevalance of Hepatozoon infections in dogs from Kyrgyzstan using polymerase chain reaction (PCR) and sequence analysis. To determine the prevelance of hepatozoonosis in dogs, a total of 170 blood samples were applied to PCR to amplify a fragment of 666 bp found in 185 SSU rRNA gene of Hepatozoon spp. The PCR results shown that Hepatozoon infection rate was 28.8% (49/170) in dogs. Eleven representative positive samples were sequenced to classification of the species. The nucleotide sequences were compared to the H. canis sequences which registered in GenBank using the basic local alignment search tool. Results of sequence analyse of 11 amplicons indicated that 8 were 100% identical and the other 3 sequences shared 99% similarity with H. canis. The sequences were deposited in Genbank with accession numbers from MG917709 to MG917719. It was the first record of H. canis in dogs in Kyrgyzstan.
Doğal enfekte köpeklerde hepatozoon enfeksiyonlarının moleküler yöntemlerle araştırılması: Hepatozoon canis’in kırgızistan’da ilk tespiti
Keywords: Hepatozoonosis; Hepatozoon canis; Dog; PCR; Sequencing; Kyrgyzstan